Impact of Humic Substances on Alleviation of Soil Salinity and the Enhancement of Plant Productivity: a review - Abed, Basim; Elham Khalifa Mahmood; Abdullah M.S. Addaheri (University of Thi-Qar Journal of agricultural research, 2024)
Humic substances (HS) are a major component of organic matter in soil, and they have long been recognized for their ability to promote plant growth in a sustainable manner. Recently, there has been a lot of effort put into using multiple approaches to study the connection between the chemical structure of HS compounds and their effect on plant biological processes. Positive physiological responses at the local and systemic levels have been linked to the presence of specific functional groups in HS. Hormone-like signaling pathways are responsible for eliciting these reactions. This review was written with one goal in mind: to help readers gain a firm grasp on the research surrounding the application of HSs. The spatial arrangement of hydrophilic and hydrophobic regions, as well as the dosage, source, molecular size, degree of hydrophobicity, and aromaticity, all contribute significantly to HS’s biological efficacy. Therefore, our hypothesis explains the beneficial effect of HS in salt-affected rhizospheres, likely attributed to both direct and indirect influences on plant metabolism, soil microorganism metabolism, soil nutrient uptake dynamics, and soil physical conditions. Keywords: Humic substance, germination, salinity, plant growth